Focus on Depression in Parkinson's Disease: A Delphi Consensus of Experts in Psychiatry, Neurology, and Geriatrics. (8th February 2021) - Agüera-Ortiz, Luis; García-Ramos, Rocío; Grandas Pérez, Francisco J.; López-Álvarez, Jorge; Montes Rodríguez, José Manuel; Olazarán Rodríguez, F. Javier; Olivera Pueyo, Javier; Pelegrín Valero, Carmelo; Porta-Etessam, Jesús
Abstract : Major and minor forms of depression are significant contributors to Parkinson's disease morbidity and caregiver burden, affecting up to 50% of these patients. Nonetheless, symptoms of depression are still underrecognized and undertreated in this context due to scarcity of evidence and, consequently, consistent clinical guideline recommendations. Here, we carried out a prospective, multicentre, 2-round modified Delphi survey with 49 questions about the aetiopathological mechanisms of depression in Parkinson's disease (10), clinical features and connections with motor and nonmotor symptoms (10), diagnostic criteria (5), and therapeutic options (24). Items were assessed by a panel of 37 experts (neurologists, psychiatrists, and a geriatrist), and consensus was achieved in 81.6% of them. Depressive symptoms, enhanced by multiple patient circumstances, were considered Parkinson's disease risk factors but not clinical indicators of motor symptom and disease progression. These patients should be systematically screened for depression while ruling out both anhedonia and apathy symptoms as they are not necessarily linked to it. Clinical scales (mainly the Geriatric Depression Scale GDS-15) can help establishing the diagnosis of depression, the symptoms of which will require treatment regardless of severity. Efficacious and well-tolerated pharmacological options for Parkinson's comorbid depression were selective serotonin reuptake inhibitors (especially sertraline), dual-action serotonin and norepinephrine reuptake inhibitors (venlafaxine, desvenlafaxine, and duloxetine), multimodal (vortioxetine, bupropion, mirtazapine, and tianeptine), and anti-Parkinsonian dopamine agonists (pramipexole, ropinirole, and rotigotine). Tricyclic antidepressants and combining type B monoamine oxidase inhibitors with serotonergic drugs have serious side effects in these patients and therefore should not be prescribed. Electroconvulsive therapy was indicated for severe and drug-refractory cases. Cognitive behavioural therapy was recommended in cases of mild depression. Results presented here are useful diagnostic and patient management guidance for other physicians and important considerations to improve future drug trial design.